The prognostic significance of tertiary lymphoid structures in oral squamous cell carcinomas: a systematic review - Ribeiro, V.; Teillaud, J-L.; Dieu-Nosjean, M-C.; Lescaille, G.; Rochefort, J. (Frontiers in Oral Health, 2025)
IntroductionUpper aerodigestive tract cancers are prevalent, with a global incidence surpassing 500,000 new cases in 2018. Among these, oral squamous cell carcinomas (OSCC) constitute the majority. OSCC has a low 5-year survival rate due to late-stage diagnosis. Risk factors include alcohol and tobacco use. However, non-smokers and non-drinkers are also affected, especially young patients with tongue cancer. The impact of tumor microenvironment (TME) and tumor-infiltrating lymphocytes (TILs) on OSCC prognosis remains debated. Remarkably, Tertiary Lymphoid Structures (TLS) identified in solid tumors have shown associations with favorable outcomes, yet their prognostic significance in OSCC remains understudied.ObjectiveThus, this systematic review aims to explore the value of TLS in OSCC reported in the literature.MethodA scoping review was conducted and six retrospective cohort studies involving 1,203 patients met the inclusion criteria.ResultsPredominantly male patients, with an average age of 49.3 years were included. Immunohistochemistry was the primary method to identify TLS, present in 21% up to 100% of cases. TLS were predominantly located in the peri-tumoral area (75.4%–84.8%) compared to the intra-tumoral area (33.8%–33.9%). Our review shows that the presence of TLS is associated with improved survival in OSCC.DiscussionHowever, variations in TLS detection and classification methods across studies introduce potential biases, hindering direct comparisons between findings. For instance, reports that are based solely on examining HES-stained slides for TLS identification may raise reliability concerns. Standardization of methodologies is imperative to ensure consistency in criteria utilization, thereby facilitating meaningful data comparisons.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023428010, PROSPERO (CRD42023428010).